ANALISIS DELEGATION OF AUTHORITY DAN HUMAN RELATION PENGARUHNYA KINERJA PEGAWAI KANTOR GUBERNUR SUMATERA UTARA - Tazri, Agung Khairul; Harmen, Hilma (Relawan Jurnal Indonesia, 2024)
The aim of this quantitative research is to find out how interactions between people and delegation of authority influence the work results of North Sumatra governor's office staff. A sample of fifty-five employees was used in all sampling techniques. This research uses Measurement Model Evaluation (Outer Model), Structural Model Evaluation (Inner Model), and Smart PLS 4.0 for Hypothesis Testing as data collection tools. Delegation of Authority has a good and significant influence on the performance of North Sumatra Governor's Office employees by 46.9%, in accordance with the results of research on hypothesis testing. Within the Office of the Governor of North Sumatra, human relations have a good and significant impact on employee performance by 49.9%.